Yorùbá Yé Mi - Mosadomi, Fehintola (Open textbook library., 2014)
The Yorùbá Yé Mi textbook, combined with an open access, multi-media website at http://www.coerll.utexas.edu/yemi, is an interactive, communicative, introductory Yorùbá program. It provides college/university students with basic listening, speaking, reading, and writing skills of language learning in Yorùbá. It exposes the learner not only to Yorùbá language in meaningful situations but also to the culture of the Yorùbá-speaking people of South-western Nigeria. It contains effective techniques for teaching and learning Yorùbá including tones, and is user friendly in its approach.